EVALUASI IMPLEMENTASI KURIKULUM DAN PROGRAM UNGGULAN PENDIDIKAN ISLAM: STUDI KASUS DI SDN PERMATA BIRU - Nurdita Indriawati; Mulyawan Safwandy Nugraha (STKIP Subang, 2026)
This research is motivated by the rapid shift toward digital transformation in education and the urgent need for effective pedagogical tools in public institutions. While many studies focus on integrated curricula in private religious schools, literature specifically examining the implementation of Islamic education excellence programs within State Elementary Schools (SDN) remains limited. Such institutions often face structural constraints, including limited academic time and resources. The primary objective of this study is to comprehensively evaluate the implementation of the curriculum and Islamic education excellence programs at SDN Permata Biru using a gap analysis to identify discrepancies between ideal policy and practical reality. A qualitative descriptive approach with a case study design was employed, utilizing the CIPP (Context, Input, Process, Product) evaluation model as the analytical framework. Data were gathered through a triangulation of methods, including participatory observation, semi-structured in-depth interviews with key stakeholders, and rigorous documentation studies. The findings reveal a positive anomaly where SDN Permata Biru successfully created a synchronization model between the National Curriculum (Kurikulum Merdeka) and religious programs, which are integrated organically into the school culture rather than being mere additions. Statistical data shows high achievement levels, such as 98% in congregational prayer habituation and 82% in Tahfidz Al-Qur'an. Notably, the program increased student motivation and enthusiasm instead of adding cognitive burden. The implications of this study highlight that instructional leadership and managerial flexibility are vital for overcoming bureaucratic barriers in state schools. This research provides a strategic blueprint for other public schools to harmonize national standards with religious character building effectively. Keywords: Case study, CIPP model, curriculum integration, Islamic education, state elementary school.